2012
DOI: 10.1109/twc.2012.090312.120461
|View full text |Cite
|
Sign up to set email alerts
|

RNP-SA: Joint Relay Placement and Sub-Carrier Allocation in Wireless Communication Networks with Sustainable Energy

Abstract: Abstract-Green energy is emerging as a promising alternative energy source to power network devices in next-generation wireless networks. Different from traditional energy, green energy is replenished from nature, e.g., solar and wind, and is highly dependent on the capacities and locations of the electronic devices. As such, the fundamental design criterion in the network deployment and management is shifted from energy efficiency to energy sustainability due to the sustainable nature of green energy. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 24 publications
0
38
0
Order By: Relevance
“…Due to individual merits and demerits of PV and WECS, hybrid PV-wind generation system with storage backup unit has proved to be reliable power source [55,56] to feed electrical loads that need high reliability [57] and uninterrupted power supply [58]. Hybrid generation has been considered preferred choice for remote systems like radio telecommunication, satellite earth stations, or sites isolated from conventional power system [59,60].…”
Section: Decentralized Hybrid Wecs-pv Generationmentioning
confidence: 99%
“…Due to individual merits and demerits of PV and WECS, hybrid PV-wind generation system with storage backup unit has proved to be reliable power source [55,56] to feed electrical loads that need high reliability [57] and uninterrupted power supply [58]. Hybrid generation has been considered preferred choice for remote systems like radio telecommunication, satellite earth stations, or sites isolated from conventional power system [59,60].…”
Section: Decentralized Hybrid Wecs-pv Generationmentioning
confidence: 99%
“…There are many existing works focus on energy efficiency in wireless networks with traditional energy sources, while energy sustainability in sustainable wireless networks has not been well studied. Thus, we are motivated to revisit the research issues including energy modeling, resource allocation and network planning under the new dimension of energy sustainability in sustainable wireless networks [12,14,29] in this brief. We first present the characteristics of green energy supply.…”
Section: Fig 11 An Illustration Of Green Bsmentioning
confidence: 99%
“…Therefore, it is critical to guarantee the energy sustainability by jointly considering energy charging and discharging capabilities in sustainable wireless networks. Some works [14,26,32] re-visit the resource allocation problem to achieve the network sustainability in sustainable wireless networks. In [33], power saving mechanism and control algorithm design are considered in solar-powered WLAN mesh networks.…”
Section: Resource Allocationmentioning
confidence: 99%
“…Since the publication of that study, resource management for sustainable wireless networks has been studied in multiple contexts. In [1] and [3], the AP placement problem 0733-8716/14/$31.00 c 2014 IEEE has been re-visited in the context of sustainable WLAN mesh networks, in which a minimal number of APs with renewable energy sources are deployed in an area such that the quality of service (QoS) requirements of users can be fulfilled. In [4], by comparing sustainability performance of various routing algorithms, it is shown that traditional routing strategies without considering energy charging capability achieve poor performance; it is crucial to adapt routing decisions to the time varying energy supplies.…”
Section: Introductionmentioning
confidence: 99%